Análisis de la red de la CNT EP para la implementación de servicios integrados mediante tecnología MPLS - Tapia Castañeda, Fredy Germán (2012)
In the present project there will be analyzed the feasibility that has the Network that nowadays the CNT EP to support the implementation of additional services to the telephony since they are those of multimedia, this network of additional services nowadays is known as NGN or Networks of New Generation. The technology most adapted for this implementation nowadays is that of MPLS for his multiple benefits that we it will be presenting in every chapter, in addition there will be realized a technical and economic analysis of feasibility by costs of equipment more adapted for the execution of this project